2012
DOI: 10.1111/j.1744-6198.2012.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy With Application to Nursing Education: A Concept Analysis

Abstract: Nursing literature suggests increasing students' perceived self-efficacy will help to narrow the theory-practice gap. Self-efficacy is a cognitive variable that affects performance behaviors and affective processes. Perceived self-efficacy can be influenced by a direct experience, vicarious experience, or verbal persuasion. Individuals with high levels of self-efficacy demonstrate the defining attributes of confidence, perceived capability, and perseverance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 28 publications
(69 reference statements)
0
42
0
2
Order By: Relevance
“…[1][2][3] Students with higher SE expectancies participate in learning activities more enthusiastically, they put more effort, struggle with challenging situations and display better performance when compared to those students with low SE expectancies. 4 SE is the main determinant and central concept of education.…”
Section: Self Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Students with higher SE expectancies participate in learning activities more enthusiastically, they put more effort, struggle with challenging situations and display better performance when compared to those students with low SE expectancies. 4 SE is the main determinant and central concept of education.…”
Section: Self Efficacymentioning
confidence: 99%
“…2,5,6 The relationship between effective learning, academic performance and SE in nursing education has been clearly defined. 1,2,7,8 In literature, those studies investigating the role of SE beliefs in the education of nurses and midwives have been mainly conducted in the field of nursing. However in a study it was found that first year nursing and midwifery students have equal level of SE.…”
Section: Self Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Robb's study shows that an increase in SE level resolves the gap between theory and practice and makes it easier to gain clinical skills. Robb (2012), in his paper reviewing publications between 1982 and 2010, affirms that Bandura's definition of the cognitive dimension of SE belief and its four main sources comply with nursing education. It is common to use these sources for enhancing SE in nursing education.…”
Section: The Concepts Of Problem-solving and Self-efficacymentioning
confidence: 99%
“…According to Bandura (1997), SE belief affects people's decisions in determining a goal, how much they will struggle to reach that goal, and how long they will be able to face the difficulties they encounter or whether they will avoid such difficulties. The concept of SE is also defined as the main concept of nursing education (Robb, 2012). Robb's study shows that an increase in SE level resolves the gap between theory and practice and makes it easier to gain clinical skills.…”
Section: The Concepts Of Problem-solving and Self-efficacymentioning
confidence: 99%